Pemanfaatan Quick Count pada Perhitungan Suara Pemilukada di Masa Pendemi Covid - dwi cahyani; Shendy S. Igirisa (LP2M IAIN Sultan Amai Gorontalo, 2022)
This study aimed to determine the effectiveness of the quick count application in regional head elections in Bone Bolabgo Regency. The implementation method consisted of the following steps: placing volunteers who went directly to the selected polling station to be sampled, conducting a literature review by searching for theories, books, and journals that had researched the same topic, and designing applications that were used to calculate vote acquisition. All computer operating systems were compatible with applications created using Microsoft Office Excel. The results indicated that the Quick Count application was effective and could give the Regional Head General Election results approximately three hours after vote counting started at the polling station.